Impact of COVID-19 on gastrointestinal endoscopy practice in India: a cross-sectional study - Goenka, Mahesh K.; Afzalpurkar, Shivaraj; Ghoshal, Uday C.; Guda, Nalini; Reddy, Nageshwar (Endoscopy International Open, 2020)
Background and study aims Gastrointestinal endoscopy, being an aerosol-generating procedure, has the potential to transmit Severe Acute Respiratory Distress Syndrome Corona Virus-2 (SARS-CoV-2) during the current pandemic. Adequate knowledge is the key to prevention. A survey, perhaps the first, was conducted among Indian endoscopists to assess the impact of Coronavirus Disease (COVID)-19 on gastroinestinal endoscopy practice in the country.Methods From April 24 to 28, 2020, an electronic survey (using Google Form) was conducted with 23 questions (single or multiple answers) on: (1) endoscopy practice before the pandemic; (2) knowledge about COVID-19; and (3) its impact on endoscopy practice.Results Responses were received from 375 of 1205 (31.1 %) endoscopists. Most (35.7 %) were young (31–40 years), practicing in corporate multi-speciality hospitals (44.6 %) or independent practice set-up (17.7 %) in metropolitan cities (55.6 %) and urban areas (42.3 %). In most units (75.4 %), fewer than 10 % of procedures performed are endoscopies, as compared to before the pandemic. A reduction in volume of endoscopy related to restriction of the routine procedures by the latest guideline was reported by 86.9 % of respondents. Most are using N95 masks (74.7 %) and/or complete personal protective equipment (PPE, 49.2 %) during endoscopic procedures. Only 18.3 % of respondents had access to negative pressure rooms either within (5.4 %) or outside (12.9 %) the usual endoscopy suite.Conclusion Endoscopy units in India are performing fewer than 10 % of their usual volumes due to current restrictions. Resources to follow current international guidelines, including use of negative pressure rooms and PPE, are limited. Alternate measures are needed to keep up the services.